Aerodynamic Parameter Identification Based Adaptive Control for Morphing Vehicle - CAO Chengyu; LIAO Yuxin; CAO Yuteng; LI Jun (Kongzhi Yu Xinxi Jishu)
Aiming at the attitude control problem of morphing vehicle, a novel adaptive control method based on online identification of aerodynamic parameters is proposed, considering the influence of aerodynamic parameter uncertainty and external disturbance. Firstly, aerodynamic parameter identification model and control-oriented model are established based on the motion model of morphing vehicle. Then, an adaptive control method based on online identification of aerodynamic parameters is proposed. Specifically, an online identification method of aerodynamic parameters is designed based on the extended Kalman filter algorithm, which realizes high-precision online identification of unknown aerodynamic parameters in the presence of system noise and measurement noise. A control scheme based on sliding mode control and disturbance observer is proposed, and the online identification results of aerodynamic parameters are used to update the model parameters in the controller, realizing the adaptive attitude control of the morphing vehicle. By the proposed online identification method of aerodynamic parameters, an online identification simulation of identifiable aerodynamic parameters is carried out on the basis of the identifiability analysis of aerodynamic parameters, and the simulation results show that the identification method can ensure that the identification relative error of more than 90% of aerodynamic parameters is less than 5%, which shows high identification accuracy. Finally, the reentry attitude adaptive control simulation is carried out, and the proposed adaptive control method based on online identification of aerodynamic parameters is compared with the sliding mode control method, dynamic surface control method and the control method based on disturbance observer. The results show that the proposed method has the strongest disturbance rejection capability and the highest control accuracy under the condition of large aerodynamic parameter uncertainty and external disturbance.